Estudos visando a síntese estereosseletiva de derivados de piran-2-onas com marcantes atividades biológicas - Suélen Karine Sartori (2021)
Lactones are cyclic esters that are found in the chemical structures of several natural products. It is a class of organic compounds of great importance due to its biological activities, their main exponent being the d-lactones. Among these, a,b-unsaturated d-lactones, also known as 5,6-dihydro-2H-pyran-2-ones, are the ones that stand out the most. The (-)-cleistenolide (1), (-)-argentilactone (92) and (-)-massoialactone (93) are important members of this class of compounds with marked biological activities, such as antibacterial and antifungal. In view of this, the present work aimed to develop a new synthetic route aiming at obtaining these a,b-unsaturated d-lactones, using D-mannitol, a natural polyol, as a synthetic precursor. These studies were distributed in two chapters: the first portrays the development of synthetic routes aiming at the synthesis of (-)-1, and the second for the syntheses of (-)-92 and (+)-93, the enantiomer of the natural product. The syntheses of these lactones were envisaged using D-mannitol as the source of the stereogenic centers present in these molecules. In studies involving the synthesis of (-)-1, twenty-seven compounds were obtained, of which 15 have not been described in the literature. Among these, olefin Z 55, a key and unprecedented intermediary for the synthesis of (-)-1, obtained with 89% yield using Horner-Wadsworth-Emmons olefination reaction, modified by Ando, from aldehyde 54 and phosphonate 58. With this olefin, it was possible to prepare 11 synthetic derivatives, four of them (compounds 64, 70, 71 and 79) are a,b-unsaturated g-lactones that have not been previsouly reported and they were obtained with yields ranging from 63 to 91%. Obtaining these is of great value, since g-lactonic rings can be converted into d-lactonic rings. In addition to these, one unpublished, product containing furan ring was obtained from 1,4-addition reaction to the a,b-unsaturated carbonyl system. With the studies carried out to obtain (-)-92 and (+)-93, more 14 compounds were obtained, among which, thirteen are unpublished. Among them, nitriles 143 and 150 are advanced synthetic intermediates for the synthesis of (-)-92 and (+)-93 and were obtained with 75% yield. These products were obtained from their respective olefins 128 and 129, from Wittig's olefin reaction between (R)-glyceraldehyde ketal 34 and Wittig's salts 130 and 131, using improved methodology during the development of this work.